AKULTURASI BUDAYA PADA TRADISI KALANG OBONG DALAM PERSPEKTIF AGAMA ISLAM - Hithna Rohadatul Aisyi; Nehru Millat Ahmad (Universitas Nahdlatul Ulama Surakarta, 2026)
This study examines cultural acculturation in the Kalang Obong tradition in Tratemulyo Village, Kendal, from the perspective of Islam. The Kalang Obong tradition, which involves the rite of honoring the deceased through the burning of dolls and belongings belonging to the deceased, shows the synergy between elements of local culture, Hinduism, and Islam. The research method used is an ethnographic approach with phenomenological studies to understand the meaning of local community actions. The results of this study show how the Kalang people can maintain their traditions while adapting to Islamic religious values, creating a space for dialogue between cultural preservation and religious commitment.